Assessment of dynamic pressure and wave forces on vertical-caisson type breakwater. Issue 2 (2nd February 2022) - Kumaran, V.; , Manu; Rao, Subba
Abstract: The design and construction of coastal structures such as breakwaters, at great water depths is rapidly increasing as a result of the increasing draught of large vessels and off-shore land reclamations. Vertical caisson breakwaters may be the best alternative compared to ordinary rubble mound breakwaters in larger water depths, in terms of performance, total costs, environmental aspects, construction time and maintenance. To fulfilling the functional utility and impact of the structure on the sea environment, it is necessary to study the hydraulic performance. This can be found by field investigation, numerical simulations and by physical modelling. Scale modelling techniques are used to study various coastal engineering problems. This article presents the results obtained by conducting series of experiments in two-dimensional wave flume to assess the hydrodynamic performance of vertical-caisson breakwater, which is made of concrete, with the protection of toe. The dynamic pressure distribution, wave runup, wave reflection, wave forces and stability parameter on the vertical caisson breakwater are discussed. The maximum wave force on the wall breakwater is calculated from measured pressure values and is compared with the forces calculated by Goda's and Sainflou wave theories.